Information Accrual From the Period Preceding Racket-Ball Contact for Tennis Ground Strokes: Inferences From Stochastic Masking - Jalali, Sepehr; Martin, Sian E.; Ghose, Tandra; Buscombe, Richard M.; Solomon, Joshua A.; Yarrow, Kielan (Frontiers in Psychology, 2019)
Previous research suggests the existence of an expert anticipatory advantage, whereby skilled sportspeople are able to predict an upcoming action by utilising cues contained in their opponent’s body kinematics. This ability is often inferred from “occlusion” experiments: Information is systematically removed from first-person videos of an opponent, for example by stopping a tennis video at the point of racket-ball contact, yet performance, such as discrimination of shot direction, remains above chance. Here, we assessed the expert anticipatory advantage for tennis ground strokes via a modified approach, known as “bubbles”, in which information is randomly removed from videos at in each trial. The bubbles profile is then weighted by trial outcome (i.e. a correct vs. incorrect discrimination) and combined across trials into a classification array, revealing the potential cues informing the decision. In two experiments (both with N = 34 skilled tennis players) we utilised either temporal or spatial bubbles, applying them to videos running from 0.8 s to 0 s before the point of racket-ball contact (cf. Jalali et al., 2018). Results from the spatial experiment were equivocal, but somewhat suggestive of accrual from the torso region of the body. Results from the temporal experiment, on the other hand, were clear: information was accrued mainly during the period immediately prior to racket-ball contact. This result is broadly consistent with prior work using non-stochastic approaches to video manipulation, and cannot be an artifact of temporal smear from information accrued after racket-ball contact, because no such information was present.